2015
DOI: 10.1002/anie.201505244
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophosphination of CO2 and Subsequent Formate Transfer in the 1,3,2‐Diazaphospholene‐Catalyzed N‐Formylation of Amines

Abstract: Hydrophosphination of CO2 with 1,3,2-Diazaphospholene (NHP-H; 1) afforded phosphorus formate (NHP-OCOH; 2) through the formation of a bond between the electrophilic phosphorus atom in 1 and the oxygen atom from CO2 , along with hydride transfer to the carbon atom of CO2 . Transfer of the formate from 2 to Ph2 SiH2 produced Ph2 Si(OCHO)2 (3) in a reaction that could be carried out in a catalytic manner by using 5 mol % of 1. These elementary reactions were applied to the metal-free catalytic N-formylation of am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(119 citation statements)
references
References 115 publications
3
114
0
2
Order By: Relevance
“…Note that most of the P À Hh ydrides examined, except for 1f,a re much more reactive than those commonly used NaBH 4 ,dihydropyridines and metal hydrides, with 1a (N = 25.54) as the most nucleophilic donor ever quantified by Equation (1). [8] According to the nucleophilicity parameters disclosed here, 1a should be roughly 10 2 times more reactive than 1d (N = 18.74). [3] Thep owerfulness of 1a was also evidenced in other applications such as in catalytic reductions of imines, [5a] azocompounds, [7] pyridines, [9a] and CO 2 .…”
Section: Zuschriftenmentioning
confidence: 75%
See 1 more Smart Citation
“…Note that most of the P À Hh ydrides examined, except for 1f,a re much more reactive than those commonly used NaBH 4 ,dihydropyridines and metal hydrides, with 1a (N = 25.54) as the most nucleophilic donor ever quantified by Equation (1). [8] According to the nucleophilicity parameters disclosed here, 1a should be roughly 10 2 times more reactive than 1d (N = 18.74). [3] Thep owerfulness of 1a was also evidenced in other applications such as in catalytic reductions of imines, [5a] azocompounds, [7] pyridines, [9a] and CO 2 .…”
Section: Zuschriftenmentioning
confidence: 75%
“…Gudat and co-workers seminal work demonstrated that 1a is af orm of super-hydride, [3] yet with common features of organic reagents, [4] such as relatively low cost and good solubility in organic media. Consequently,an umber of N-heterocyclic phosphorus hydrides ( Figure 1) and their analogues have been developed in recent years,rendering many originally infeasible reactions to occur under metal-free conditions,s uch as reductions of polar olefins, [5] imines, [5a] ketones, [6] and azo compounds, [7] valorization of CO 2 , [8] and hydroboration of pyridines. Consequently,an umber of N-heterocyclic phosphorus hydrides ( Figure 1) and their analogues have been developed in recent years,rendering many originally infeasible reactions to occur under metal-free conditions,s uch as reductions of polar olefins, [5] imines, [5a] ketones, [6] and azo compounds, [7] valorization of CO 2 , [8] and hydroboration of pyridines.…”
Section: Contrastingwiththewell-knownproticreactivityofconven-mentioning
confidence: 99%
“…Whereas the N‐formylation of amines with CO 2 may be achieved by using hydrogen as the reducing agent, harsh reaction conditions and poor functional group tolerance have led to the employment of other reducing agents such as hydrosilanes (Scheme a) . The N‐formylation of amines with hydrosilanes has been achieved with transition‐metal‐based catalysts (e.g., copper and iron) and a number of organocatalysts …”
Section: Methodsmentioning
confidence: 99%
“…Owing to their intriguing applications as various biological intermediates and raw materials for the synthesis of various chemicals, several catalytic methods have been developed for the synthesis of N ‐formamides . Among all the reported methods, the synthesis of N ‐formamides by using the CO 2 reduction method is considered as one of the most prominent pathways from the industrial as well as academic point of view, in which various reducing agents such as H 2 , silane, and borane are used repeatedly …”
Section: Resultsmentioning
confidence: 99%